Mutations Closer to the Active Site Improve the Promiscuous Aldolase Activity of 4‐Oxalocrotonate Tautomerase More Effectively than Distant Mutations. (30th May 2016) - Rahimi, Mehran; van der Meer, Jan‐Ytzen; Geertsema, Edzard M.; Poddar, Harshwardhan; Baas, Bert‐Jan; Poelarends, Gerrit J.
Abstract: The enzyme 4‐oxalocrotonate tautomerase (4‐OT), which catalyzes enol–keto tautomerization as part of a degradative pathway for aromatic hydrocarbons, promiscuously catalyzes various carbon–carbon bond‐forming reactions. These include the aldol condensation of acetaldehyde with benzaldehyde to yield cinnamaldehyde. Here, we demonstrate that 4‐OT can be engineered into a more efficient aldolase for this condensation reaction, with a >5000‐fold improvement in catalytic efficiency ( k cat / K m ) and a >10 7 ‐fold change in reaction specificity, by exploring small libraries in which only "hotspots" are varied. The hotspots were identified by systematic mutagenesis (covering each residue), followed by a screen for single mutations that give a strong improvement in the desired aldolase activity. All beneficial mutations were near the active site of 4‐OT, thus underpinning the notion that new catalytic activities of a promiscuous enzyme are more effectively enhanced by mutations close to the active site. Abstract : Closer is better : Systematic mutagenesis of all amino acid residue positions in 4‐oxalocrotonate tautomerase demonstrated that for the aldolase activity of this promiscuous enzyme, mutations at His6, Met45, and Phe50, close to the active site (near Pro1), improve the enzyme more effectively than distant ones.